2013
DOI: 10.2478/pjvs-2013-0029
|View full text |Cite
|
Sign up to set email alerts
|

Changes in expression of calbindin 28 kDa in the small intestine of red kidney bean (Phaseolus vulgaris) lectin-treated suckling piglets

Abstract: Calbindin (CB) is a calcium binding protein playing a role in calcium uptake and anti-apoptotic cellular protection. The expression of CB was immunohistochemically studied in the small intestine of normal and red bean kidney lectin-treated suckling piglets. In the duodenum and jejunum (but not ileum) of lectin-treated animals overexpression of CB was noted in chromogranin A-immunoreactive (CgA-IR) neuroendocrine (NE) cells. In both control and experimental group a small population of CB-IR NE cells exhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…All images were obtained with a digital color camera (DP-70, Olympus) using the Cell^M image system software (Olympus). In all segments of the small and large intestines of the control and experimental animals, the numbers of NEC IR for serotonin, GLP1, or somatostatin were assessed by cell counting according to a protocol described elsewhere (39). Briefly, cell counts were performed in 10 mm long section of non-interrupted and not damaged intestinal mucosa (at least 5 slides from intestines of each animal from every group).…”
Section: Methodsmentioning
confidence: 99%
“…All images were obtained with a digital color camera (DP-70, Olympus) using the Cell^M image system software (Olympus). In all segments of the small and large intestines of the control and experimental animals, the numbers of NEC IR for serotonin, GLP1, or somatostatin were assessed by cell counting according to a protocol described elsewhere (39). Briefly, cell counts were performed in 10 mm long section of non-interrupted and not damaged intestinal mucosa (at least 5 slides from intestines of each animal from every group).…”
Section: Methodsmentioning
confidence: 99%
“…Control sections showed no detectable labelling. Previously described counting protocol was applied in the image analysis (30). Briefly, in the sections with no visible damage of mucosa, all EC were identified and counted.…”
Section: Methodsmentioning
confidence: 99%
“…The distribution and number of rat EEC were locally changed dependently on the diet type and the presence of the gut microflora (27). Recently, it has been also found that the number of calbindin-containing EEC increases in suckling pigs treated with lectin (30).…”
Section: Introductionmentioning
confidence: 99%